2019
DOI: 10.1186/s12985-019-1192-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cucurbit chlorotic yellows virus P4.9 as a possible movement protein

Abstract: Background Cucurbit chlorotic yellows virus (CCYV) is a bipartite cucurbit-infecting crinivirus within the family Closteroviridae . The crinivirus genome varies among genera. P4.9 is the first protein encoded by CCYV RNA2. P5, which is encoded by LIYV, is necessary for efficient viral infectivity in plants; however, it remains unknown whether CCYV P4.9 is involved in movement. Finding In this study, we used green fluorescent protein (GFP) to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The plasmodesmata (PD) is the critical macromolecule transport corridor in plant cell walls. Because of its size exclusion limit (SEL), PD is a bottleneck during plant virus infections [42]. Many studies have demonstrated that plant virus infections can induce callose accumulation around PDs, leading to a restriction of virus intercellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmodesmata (PD) is the critical macromolecule transport corridor in plant cell walls. Because of its size exclusion limit (SEL), PD is a bottleneck during plant virus infections [42]. Many studies have demonstrated that plant virus infections can induce callose accumulation around PDs, leading to a restriction of virus intercellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…The changed adenine and guanine have been proved that utilizing for RNA synthesis. CCYV is a single strain RNA virus with a bipartite genome [ 42 ]. Our recent work proved that the titers of CCYV within host plant increased from 10 to 30 dpi [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCYV is regulated by a protein P4.9 [29]. As a result of systemic infection, plants usually develop interveinal yellowing symptoms typical of CCYV [30].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…In general, the cell-to-cell movement of plant viruses depends on the movement protein (MP) that modifies the size exclusion limit of the plasmodesmata (PD) to facilitate viral genome transport to adjacent, uninfected cells [27,28]. Similarly, other research has shown that the systemic movement of CCYV is regulated by a protein P4.9 [29]. As a result of systemic infection, plants usually develop interveinal yellowing symptoms typical of CCYV [30].…”
Section: Introductionmentioning
confidence: 99%